School inclusion in youth and adult education - Rodriguez, Eglaucimara Oliveira; Dutra, Alessandra; Storto, Letícia Jovelina (Revista Eletrônica de Educação, 2017)
This study investigates teachers’ perceptions about the assistance provided to students with special educational needs, developmental disorders and high skills or giftedness at a state educational institution in Londrina (Brazil) which offers exclusively Youth and Adult Education modality. For this, we applied an instrument to collect data with 24 participants whose questions were about school inclusion in Youth and Adult Education. The results showed that most teachers did not receive specific training to support pupils with special educational needs. These professionals reported that they are dissatisfied with the developed work, highlighting the lack of training and capacitating programs as the main cause. Data also showed that, in seeking help and support for professional practice, teachers usually rely on colleagues with specific training and the school teaching staff. Several points highlighted as barriers for effective school inclusion are related to questions present in any heterogeneous class and not specifically with students with special educational needs. Thus, it is believed that the inclusion in the school environment can be a reality and the teacher is a key element in the consolidation of this process. Keywords: Education. Adult education and literacy. Inclusion. Teacher training. References ALMEIDA, Dulce Barros de et al. Política educacional e formação docente na perspectiva da inclusão. Educação. CE/USFM. Santa Maria/RS, v. 32, n. 2, 2007, p. 327-342. Disponível em: <http://coralx.ufsm.br/revce/revce/2007/02/a4.htm>. Acesso em: fev. 2013. BRASIL. Lei nº 13.146, de 6 de julho de 2015. Institui a Lei Brasileira de Inclusão da Pessoa com Deficiência (Estatuto da Pessoa com Deficiência). Disponível em: <http://www.planalto.gov.br/ccivil_03/_ato2015-2018/2015/Lei/L13146.htm>. Acesso em: nov. 2016. BRASIL. Lei nº 12.796, de 4 de abril de 2013. Altera a Lei no 9.394, de 20 de dezembro de 1996, que estabelece as diretrizes e bases da educação nacional, para dispor sobre a formação dos profissionais da educação e dar outras providências. Disponível em: <http://www.planalto.gov.br/ccivil_03/_ato2011-2014/2013/lei/l12796.htm>. Acesso em: dez. 2014. DUTRA, Claudia Pereira et al. Política nacional de educação especial na perspectiva da educação inclusiva. Inclusão: Revista de Educação Especial, Brasília, v. 4, n. 1, p. 7-17, jan./jun. 2008. Disponível em: <http://portal.mec.gov.br/seesp/arquivos/pdf/revinclusao5.pdf>. Acesso em: nov. 2016. ENS, Romilda T. Significados da pesquisa segundo alunos e professores de um curso de Pedagogia. 2006. 138f. Tese (Doutorado em Educação - Psicologia da Educação) - Pontifícia Universidade Católica de São Paulo. São Paulo, 2006. MITLLER, Peter. Educação inclusiva: contextos sociais. Porto Alegre: Artmed, 2003. NOZI, Gislaine Semcovici; VITALIANO, Célia Regina. Saberes docentes e o processo de inclusão de alunos com necessidades educacionais especiais. In: LIMA, Angela Maria de Souza et al. Inclusão: debates em diferentes contextos. Londrina: EDUEL, 2013. p. 28-36.